THE INFLUENCE OF BRQ AND BRAND LOVE ON REPURCHASE INTENTION AND WOM IN LOCAL FOOD - Ali Wardhana; Alice Kumala Darmadi; Tristano Aviel Sunara (FEB Universitas Sam Ratulangi Manado, 2023)
This study focuses on the effect of brand love and brand relationship quality on repurchase intention and positive word-of-mouth (WOM) for local food brands in Indonesia. Although some industries, including the food and beverage industry, continued to grow during the COVID-19 pandemic, local food brands face challenges in competing with foreign brands that dominate the industry. To sustain profit and compete effectively, local food brands need to have a competitive and creative strategy, such as building brand strength. Brand strength can be developed through building brand-consumer relationships, which are measured by brand relationship quality and brand love. Brand Relationship Quality (BRQ) is an emotional bond that develops between consumers and their preferred brands over time. It encompasses three dimensions: trust, satisfaction, and commitment. BRQ is built on the concepts of brand trust, satisfaction, and commitment, which are all crucial for building strong and lasting brand-consumer relationships. Brand love, on the other hand, is defined as the degree of emotional attachment of a consumer to a brand. It is measured by passion for the brand, attachment to the brand, positive evaluation of the brand, positive emotions in response to the brand, and expressions of love for the brand. Brand love has a positive impact on WOM and repurchase intention. This study aims to evaluate the significance of brand love and brand relationship quality in building brand loyalty for local food brands. The findings of this study will provide insights for local food brands to build and maintain strong relationships with their consumers, leading to sustained profit and competitiveness in the industry.